2011
DOI: 10.1177/039463201102400217
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary and Alternative Medicine in Children with Recurrent Acute Otitis Media in Italy

Abstract: Controlling environmental factors, chemoprophylaxis, immunoprophylaxis and surgery are considered possible means of preventing recurrent acute otitis media (RAOM), but there are no available data concerning the paediatric use of complementary and alternative medicine (CAM). We evaluated the uses of CAM (homeopathy and/or herbal medicine) as means of preventing AOM in children with a history of RAOM. Eight hundred and forty Italian children with RAOM (~3 episodes in six months) aged 1-7 years were surveyed in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…Of the 405 respondents 229 (57%) reported lifetime CAM use. Among CAM users, the most prevalent therapies were homeopathy (25%), herbal remedies (8%), anthroposophic medicine (7%), vitamin preparations (6%), and acupuncture (5%) [26]. Similar reports have been published from the United States where CAM and HM use in children is high and continuing to increase.…”
Section: Patient Safety and The Widespread Use Of Hmsmentioning
confidence: 55%
See 1 more Smart Citation
“…Of the 405 respondents 229 (57%) reported lifetime CAM use. Among CAM users, the most prevalent therapies were homeopathy (25%), herbal remedies (8%), anthroposophic medicine (7%), vitamin preparations (6%), and acupuncture (5%) [26]. Similar reports have been published from the United States where CAM and HM use in children is high and continuing to increase.…”
Section: Patient Safety and The Widespread Use Of Hmsmentioning
confidence: 55%
“…CAM was widely seen as safe (95%) and highly effective (68%), and CAM prescribers were pediatricians in 50.7% of cases [25]. A similar study in Germany looked at CAM use in 500 children in outpatient clinics [26]. Of the 405 respondents 229 (57%) reported lifetime CAM use.…”
Section: Patient Safety and The Widespread Use Of Hmsmentioning
confidence: 99%
“…The applications of this work are several and they provide the empirical background for the independent variables used in the work presented here (28)(29)(30)(31). A relevant branch of the existing literature is related to the efficacy, safety, and also cost effectiveness of CAM (32,33). There is also some work on the use of CAM for particular diseases and on the attitude of physicians towards CAM (34,35).…”
Section: Implications For Policy Makersmentioning
confidence: 99%
“…While it is known that different types of CAM treatments entail the risk of negative interactions when combined with CDT [12], it has been shown that CAM users in general do not reflect upon risks of adverse effects or negative interactions with conventional treatments [8,13,14]. CAM studies have in particular emphasized this tendency related to the use of herbal medicine [15,16]. …”
Section: Introductionmentioning
confidence: 99%